Isolation and characterization of canine adenovirus type 2 (CAV-HN45) and its selective infection of human cervical cancer cells with preliminary oncolytic potential - Wang, Cong-Rong; Wang, Dong-Mei; Yin, Guo-You; Wang, Yan-Hong; Lu, Min; Zhang, Zhuo-Wei; Wen, Yue; Gao, Ding-Zhuo; Hong, Jun; Fu, Peng-Fei (Frontiers in Veterinary Science, 2025)
Canine adenovirus type 2 (CAdV-2) infects the respiratory tissues of dogs and induces canine infectious laryngotracheitis. CAdV-2 has a high incidence of infection and is easily co-infected with other viruses. Moreover, CAdV-2 is a mammalian adenovirus with characteristics similar to those of Human Adenovirus Type 5 (HAdV-5), making it a promising candidate for recombinant vaccine development and gene therapy applications. In this study, we isolated and identified a CAdV-2 strain (CAV-HN45) and investigated its growth characteristics and viral tropism by evaluating its infection efficiency in various cell lines. Our findings demonstrate that CAV-HN45 can effectively infect cells of swine, canine, and human origin. In vitro, CAV-HN45 efficiently infected HeLa cells and showed selective infectivity toward human cervical cancer cells, although replication capacity declined after serial passages. This study provides a reference for the future studies on adenovirus vaccine vectors with high selective expression, potentially offering promising applications in the treatment of human cancers.